Tought teff set for a boost - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Ethiopia's Institute for Agricultural Research (IAR), based in Addis Ababa, has done research on teff with encouraging results. Teff is a cereal which at pre- sent is almost unique to Ethiopia. It thrives in high altitudes and is a staple food for...